Coumarins of Ferulopsis hystrix: LC–MS Profiling and Gastroprotective and Antioxidant Activities of Skimmin and Peucenidin - Yanina G. Razuvaeva; Anyuta A. Toropova; Saizana M. Salchak; Daniil N. Olennikov (Applied Sciences, 2023)
Ferulopsis hystrix is a perennial plant of the Apiaceae family. In Buryat and Mongolian medicine, it is used as a substitute for Costus speciosus roots (ru rta), and in Tibetan medicine, it is used to cure digestive system diseases and used as a wound-healing agent. However, its metabolites and their bioactivities are still poorly understood. High-performance liquid chromatography with photodiode array detection and electrospray ionization triple quadrupole mass-spectrometric detection (HPLC–PDA–ESI–tQ–MS/MS) were used to identify approximately 42 phenolic compounds in F. hystrix, and 30 coumarins were characterized and quantified. The major compounds in F. hystrix roots were skimmin (umbelliferone 7-O-glucoside) and peucenidin (vaginidiol 3′-O-acetyl-4′-O-senecioyl ester), of which, gastroprotective and antioxidant effects were found for the first time. The abovementioned compounds exhibit a gastroprotective effect against indomethacin and steroid gastropathy by reducing the amount of damage (point, large, and strip-like erosions) in the gastric mucosa and lowering the corresponding Paul’s index. The most pronounced gastroprotective effect was exhibited by skimmin at a dose of 1 mg/kg and by peucenidin at doses of 16 and 48 mg/kg; these compounds help to limit the development of pronounced erosive–necrotic processes in the gastric mucosa. In pathological conditions, these compounds reduce malondialdehyde, increase the activity of catalase, and increase the content of reduced glutathione in the blood. Thus, this study demonstrates that F. hystrix roots are a good source of bioactive coumarins with gastroprotective potential, which supports earlier ethnopharmacological studies.